Legal Protection of Alternate Universe Authors Against Plagiarism Reviewed from MUI Fatwa No. 1/MUNAS VII/MUI/5/2005 (Case Study of Twitter Application) - Yhossy rizky akbar; Mustapa Khamal Rokan (Indonesian Interdisciplinary Journal of Sharia Economics, 2024)
This research aims to determine the legal protection for creators of alternate universe (AU) works whose works are plagiarized on Twitter social media based on the MUI Fatwa and to examine and analyze the ideal legal protection against acts of plagiarism of AU works. This research uses qualitative methods with content analysis research on social media regarding AU plagiarism on Twitter. This writing shows that there are regulations that guarantee legal certainty regarding copyright for writers who publish their stories on Twitter social media, which have been stipulated in Indonesian legal regulations.MUI Fatwa NO. 1/MUNAS VII/MUI/5/2005 concerning intellectual property rights, works containing forms must be given legal protection and the act of using, disclosing, making, using, selling, importing, exporting, circulating, handing over, providing, announcing, reproducing, plagiarizing, counterfeiting, hijacking other people's IPR without rights is injustice and is haram. The legal protection (mashun) is the same as mal (wealth). This fatwa underlines the importance of respecting copyright, maintaining intellectual integrity, and preventing acts of plagiarism. In the context of plagiarism cases on Twitter, the legal function is to protect, not only morally but also to protect and ethically regarding the consequences of plagiarism. The MUI fatwa contains norms that protect property rights holders. This provides a strong moral basis for society and Alternate universe authors to avoid or treat plagiarism seriously, along with a positive legal view that also protects intellectual property rights.